Bio-banding in youth sports: Background, concept, and application - Malina, R. M.; Cumming, S. P.; Rogol, A. D.; Coelho e Silva, M. J.; Figueiredo, A. J.; Konarski, J. M.; Koziel, S. M. (Sports Medicine, 2019)
Inter-individual differences in size, maturity status, function, and behavior among youth of the same chronological age (CA) have long been a concern in grouping for sport. Bio-banding is a recent attempt to accommodate maturity-associated variation among youth in sport. The historical basis of the concept of maturity-matching and its relevance to youth sport, and bio-banding as currently applied are reviewed. Maturity matching in sport has often been noted but has not been systematically applied. Bio-banding is a recent iteration of maturity matching for grouping youth athletes into `bands` or groups based on characteristic(s) other than CA. The percentage of predicted young adult height at the time of observation is the estimate of maturity status of choice. Several applications of bio-banding in youth soccer have indicated positive responses from players and coaches. Bio-banding reduces, but does not eliminate, maturity-associated variation. The potential utility of bio-banding for appropriate training loads, injury prevention, and fitness assessment merits closer attention, specifically during the interval of pubertal growth. The currently used height prediction equation requires further evaluation.